Case Study: Intra-Patient Heterogeneity of Aneurysmal Tissue Properties - Martufi, Giampaolo; Forneris, Arianna; Nobakht, Samaneh; Rinker, Kristina D.; Moore, Randy D.; Di Martino, Elena S. (Frontiers in Cardiovascular Medicine, 2018)
Abstract Introduction Current recommendations for surgical treatment of abdominal aortic aneurysms (AAA) rely on the assessment of aortic diameter as a marker for risk of rupture. The use of aortic size alone may overlook the role that vessel heterogeneity plays in aneurysmal progression and rupture risk. The aim of the current study was to investigate intra-patient heterogeneity of mechanical and fluid mechanical stresses on the aortic wall and wall tissue histopathology from tissue collected at the time of surgical repair. Methods Finite element analysis (FEA) and computational fluid dynamics (CFD) simulations were used to predict the mechanical wall stress and the wall shear stress fields for a non-ruptured aneurysm two weeks prior to scheduled surgery. During open repair surgery one specimen partitioned into different regions was collected from the patient’s diseased aorta according to a pre-operative map. Histological analysis and mechanical testing were performed on the aortic samples and the results were compared with the predicted stresses. Results The preoperative simulations highlighted the presence of altered local hemodynamics particularly at the proximal segment of the left anterior area of the aneurysm. Results from the post-operative assessment on the surgical samples revealed a considerable heterogeneity throughout the aortic wall. There was a positive correlation between elastin fragmentation and collagen content in the media. The tensile tests demonstrated a good prediction of the locally varying constitutive model properties predicted using geometrical variables, i.e. wall thickness and thrombus thickness. Conclusions The observed large regional differences highlight the local response of the tissue to both mechanical and biological factors. Aortic size alone appears to be insufficient to characterize the large degree of heterogeneity in the aneurysmal wall. Local assessment of wall vulnerability may provide better risk of rupture predictions.